Монгол шүлэг судлалын өнгөрсөн хийгээд ирээдүй - Галбаяр.Г (Acta Mongolica, 2014)
Since poets are seen as expression of their national soul and living scenes, it is understood that poems keep a nation’s basic mind styles. It is natural for any nation to determine their own history in the past and their future progress and development paths, having accurately studied their verse in many aspects both from outside and inside, within motivated scopes. Therefore, humankind highly respect and honor verse and comprehend it as their mirror to the past and diviner towards future.Verse must be studied well so that we could study features of verse which method and regularities it is created, besides understanding past of living, future essence, and correlations kept in poems. Because it is related to that verse represented the basic mindset styles of the nation. It keeps all aspects of national language features.Though history of Mongolian verse study had been started since the ancient times, however proper science based studies had been started from 19th century, and by 20th century many issues had been solved. Throughout the historical long terms Mongolian verse had gained quite systematized structure and due to evolution and development through many external and internal causes it has brought many issues for detailed study.We have following goals for the purpose of this speech, which are, the first of all, to make integrated analysis on all studies on Mongolian verse made so far; the second, to determine main issues that were solved through the Mongolian verse study, and the third, to define issues that need to be studied within the framework of Mongolian verse study.